Fabrication and characterization of colossal magnetoresistance manganites in bulk, single layer and trilayer thin films prepared by pulsed laser deposition technique - Navasery, Manizheh (2012)
Electronic and magnetic properties of mixed-valent manganites, Re1-xMxMnO3 (Re = rare earth, M = alkaline earth), have received a lot of attention in the last decade because of the variety of interesting phenomena exhibited by these materials. This project was aimed at studying the structure and magnetotransport properties of manganites in the form of bulk, single and trilayer thin films prepared by Pulsed Laser deposition (PLD) thechnique by using Nd-YAG laser on different substrates. A comparison study between the bulk and thin film and the effect of substrate type on the structure, morphology and magneto-transport properties of the thin films was studied. In addition the enhancement of magnetoresistance (MR) and phase transition temperature (TP) on trilayer films are investigated. In the first part, the polycrystalline targets of La2/3Ca1/3 MnO3 (LCMO), La5/8Sr3/8MnO3 (LSMO), La0.7Na0.3 MnO3 (LNMO) and Pr0.7Ca0.3 MnO3 (PCMO) were prepared by solid state reaction. All samples were characterized by X-ray diffraction (XRD, Philips). The XRD data were analyzed by Rietveld refinement technique. It was found from XRD results that the bulks (same as thin films) were single phase with the orthorhombic Pnma structure for LCMO and PCMO and rhombohedral R3C structure for LSMO and LNMO, where no detectable impurities were observed. A four point probe system which is inserted in the liquid nitrogen cryostat was used to measure the phase transition temperature TP, and magnetoresistance of samples by using Hall effect system. LCMO shows metal-insulator transition at 274 K while PCMO is an insulator. In the case of LSMO and LNMO Transition temperature TP was above room temperature. The Curie temperature was measured using the CryoBIND T AC Susceptometer. TC is found from the peak in the dχʹ/dT (where χʹ is the real part of the susceptibility) via temperature curve. TC is 94.18 K for PCMO, 330.4 2 K for LSMO, 319.79 K for LNMO and 285.76 K for LCMO manganite bulks. The PCMO sample is insulating at zero magnetic field, and has a charge ordering transition around 200 K followed by antiferromagnetic and ferromagnetic transitions respectively at 142.21 K and 94.18 K that were obtained from the real and imaginary part of AC susceptibility measurement respectively. Finally, by using the vibrating sample magnetometer (VSM, Lake shore 7400) at the maximum magnetic field (10 KG), the magnetization value was 46.24 emu/g for LSMO, 21.45 emu/g for LNMO, 5.49 emu/g for LCMO and 1.66×10-3 emu/g for PCMO bulk manganites . In the second part of this work, the manganite targets of La2/3Ca1/8MnO3 (LCMO), La5/8Ca3/8MnO3, La0.3Na0.7MnO3 (LNMO) and La5/8Sr3/8MnO3 (LSMO) were deposited on different substrates such as corning glass (Cg), silicon wafer and MgO by PLD technique. All the substrates induce in-plane strains on the films, but the lattice mismatch between the manganites and the substrate is much larger for MgO than for other substrates. Thin film samples showed a much higher resistance compared to the bulk. For LSMO/MgO the high Curie temperature of 363 K is one of the high TC in all LSMO thin films and to the best of our knowledge, it is the highest value that is reported in the literature for MgO substrates with high lattice mismatch parameter. In addition, The Curie temperature of LSMO films is around 352 K, which is one of the high TC in all LSMO films and it is the highest value that is reported in literature for low cost amorphous substrates such as glass. The Curie temperature, Tc is 292 K for LNMO/Cg, 304 K for LNMO/Si and 286K for LNMO/MgO thin films. The relatively high resistance of the polycrystalline thin film may be caused by crack-like defaults and grain boundaries. Magnetoresistance was measured via fure point probe technique using Hall effect system. The highest MR value obtained was −17.21% for LSMO/MgO film followed by −15.65% for LSMO/Si film at 80 K in a 1 T magnetic field. Transition temperature (TP) is 224 K for LSMO/MgO and 200 K for LSMO/Si film. The highest MR value obtained was −18.86% for LNMO/MgO film followed by −17.35% for LNMO/Si and 16.59% for LNMO/Cg thin film at 80 K in a 1 T magnetic field. The maximum temperature coefficient of resistance (TCR) (10.42% K-1) occurs at T = 232 K for LNMO/MgO film. To our knowledge, this is the best TCR value obtained for LNMO film deposited on the not well-matched MgO substrate. The Curie temperature, Tc is found from the peak in the dχʹ/dT via the temperature curve that is 275 K for LSMO/Si, 270 K for LCMO/MgO and 292K for LCMO/Cg thin films. The highest MR value was −24.90% for LCMO/Si thin film, -16.77% for LCMO/Cg and -15.40% for LCMO/MgO thin film at 80 K in a 1 T magnetic field. The phase transition temperature (TP) is 266 K for LCMO/Si, 209K for LCMO/MgO and 231 K for LCMO/Cg thin film. The significant observation in this study is the enhancement of magnetoresistance (MR) up to 36% in the LCMO/ PCMO/LCMO trilayer films. The reason for the enhanced MR suggested that it is due to the induced double exchange mechanism in PCMO by applying the magnetic field. The melting of the charge ordered state is associated with a huge CMR effect.